Efficient removal of reactive blue-19 dye by co-electrospun nanofibers. (10th May 2021) - Hakro, Raheel Ahmed; Mehdi, Mujahid; Qureshi, Raja Fahad; Mahar, Rasool Bux; Khatri, Muzamil; Ahmed, Farooq; Khatri, Zeeshan; Kim, Ick Soo
Abstract: The present work demonstrates the new nanofiber mats prepared through co-electrospinning of two different polymers i.e. corn protein namely Zein and Nylon-6. The composite nanofiber membrane was used as an effective adsorbent material for the removal of toxic reactive dye i.e. Reactive Blue 19 (RB19) from water solution. These co-electrospun nanofibers had good mechanical strength compared to zein nanofibers alone. Experimental results suggested that zein/nylon nanofibers have greater potential for total removal of RB19 at room temperature within 10 min of contact time from aqueous solution. The maximum capacity was found to be 61.2 mg.g −1 of nanofibers. The mechanism of RB19 removal on proposed nanofibers is mainly through hydrogen bond and electrostatic means.